Employee training and development - Noe, Raymond A. (McGraw-Hill/Irwin, 2013)
Including the strategic role of training and the use of new technologies in training, this title strikes a balance between research and real company practices. It provides students with a background in the fundamentals of training and development such as needs assessment, transfer of training, learning environment design, methods, and evaluation